PERANGKAT LUNAK OPEN SOURCE PERPUSTAKAAN DIGITAL : KOMPARASI GREENSTONE DAN GANESHA DIGITAL LIBRARY - Tri Handajani; Himawanto Himawanto (Perpustakaan Nasional RI, 2019)
The digital library which become the basic pillar of information needs in all countriesis solidly built. Because of strong ideology in its software. With an open source-based, it is interesting to study digital library applications applied in two collages from different countries. This study aimed to analyze Greenstone and Ganesha Digital Library (GDL) by using observation approaches to determine the comparison of system applications, (2) metadata and interoperability, and (3) the number of languages (user interface) provided. The result showed that Greenstone continues evolving with the latest version released in 2016, while GDL has it last feature in 2014. The compatible application types associated with greenstone look different from GDL, except for the browser system. Until the latest version, Greenstone has better interoperability than GDL shown by a numberof metadata that can interact. Viewing from the user interface, Greenstone offers broaders multilingual featurescompared to GDL. Consequently, GDL needs to improve its application performance so as to be widely used by the international public. In Indonesia, however, GDL has to deal with various software applications that are widely used by national information agencies.